Identification of A Novel Mutation of SHORT Syndrome: A Case Report - Quynh Thi Vu Huynh; Tuong Trong Luong; Ho Tran Ban; Van Tran (Clinical Case Reports)
ABSTRACT SHORT syndrome is a rare inherited disease with 34 identified pathogenic or likely pathogenic PIK3R1 mutations. The genotype–phenotype relationship remains inconsistent. Our case presents the first novel duplication that affects up to 25 nucleotides and truncates the PI3K protein, contributing valuable data to genetic understanding and characterization worldwide.